Digital Storytelling as a pedagogical Tool in Teaching and Learning Literature Case Study: First Year Students of English,Laghouat University - Sadki,Rihab; Bouakkaz,Anfal; Ben Redda,Djamel (University of Ammar Theledji -Laghouat, 2021)
Since Technology provides numerous tools that teachers can use in and out of the classroom to enhance students learning, in addition to that Teaching literature bears availability, at any moment of literary texts, and the possibility that these texts are easily accessible by students who during the learning process should be taught how to analyze, evaluate and simply to understand these texts. The purpose of this research study was to determine the impact that this technology has on the manner of study by students and on the didactic of literature by teachers. Arguing that the new technologies can best support the teaching of literature, this study provides a general framework about educational uses of digital storytelling, in addition to using it as a tool for reflective practice. . An online questionnaire is used to collect responses from a group of students to determine if they are using digital storytelling for educational purposes also if they welcome the suggestion of integrating digital storytelling tool in teaching and learning. The results show that the majority of students answered that they are not engaged in a storytelling session in literature, they also propose the inclusion of digital technologies in teaching and learning literature